Super Tuesday : Regional Politics and Presidential Primaries - Norrander, Barbara, 1954- (Book collections on Project MUSE., 2015)
Super Tuesday 1988 was the first successful attempt to get several states in one region to hold their presidential primaries on the same day. Its success -- or lack thereof -- will affect the way presidents are elected for many years to come. Reaching beyond Super Tuesday and the nominations of George Bush and Michael Dukakis, Barbara Norrander's book presents the nation's first regional primary as the latest chapter in the ever-changing system through which U.S. political parties choose their presidential candidates. Norrander's research details how changes in technology, candidate and media s.